2017
DOI: 10.5152/iao.2016.2533
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-Rich Plasma Application for Acute Tympanic Membrane Perforations

Abstract: OBJECTIVE:To assess the efficacy of the application of platelet-rich plasma (PRP) in the healing process of acute tympanic membrane perforations (TMPs). MATERIALS and METHODS:Acute TMPs were made in both the ears of 12 New Zealand rabbits. Plasma gel was applied at the right tympanic membrane (TM) of the same animal until the perforations were closed. The left TM was left untreated. On days 1, 4, 7, 10, 13, 16, 21, 28, and 35, the TMs were monitored to check the closure of perforations. The days of perforation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“… 3 Erkilet et al 12 conducted a study in which PRP administration on tympanic membrane perforations led to an improved healing time. 12 Özgürsoy et al 13 in another study, concluded that PRP was an effective autologous material for the healing process of acute tympanic membrane perforations in a rabbit model. Positive effects of using PRP was also demonstrated on fat grafts used for fat myringoplasty.…”
Section: Discussionmentioning
confidence: 99%
“… 3 Erkilet et al 12 conducted a study in which PRP administration on tympanic membrane perforations led to an improved healing time. 12 Özgürsoy et al 13 in another study, concluded that PRP was an effective autologous material for the healing process of acute tympanic membrane perforations in a rabbit model. Positive effects of using PRP was also demonstrated on fat grafts used for fat myringoplasty.…”
Section: Discussionmentioning
confidence: 99%
“…Platelet-rich plasma is essentially a concentrate of autologous platelets and rich in PDGF, TGFb1, VEGF and EGF growth factors produced by these platelets (17). There are studies demonstrating that each of these polypeptides has various roles in accelerated wound healing, enhanced immune response, increased angiogenesis, and enhanced bone regeneration (18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
“…As you know, the tympanic membrane of rabbit is located at an angle of 90°in relation to the entrance to the auditory meatus [7]. The outer bony wall of the auditory meatus was removed for more convenient access using bone forceps, and it manipulation provided a good view of the tympanic membrane without using the ear funnel (Figure 1c).…”
Section: A -Basic Sciences Pathophysiologymentioning
confidence: 99%